Empowering Islamic Religious Education for Children at MI Mambaul 'Ulum Lemah Ayu Indramayu - Siti Rosanti; Didik Himmawan (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2024)
This article discusses the concept of empowering Islamic communities through the guidance of teaching Islamic Religious Education in MI Mambaul 'Ulum, Lemah Ayu Village, Kertasemaya District, Indramayu Regency. The methods used are observation, survey and interview methods. The results of this study conclude that the empowerment of Islamic communities through the guidance of teaching Islamic Religious Education at MI MAMBAUL 'ULUM more or less provides new changes such as more varied learning styles and the introduction of learning media to class V students of MI Mambaul 'Ulum. However, there are some concepts that are not realized due to certain factors. Factors that influence the concept of empowerment are a. Supporting factors: enthusiasm of teachers and students in receiving work programs. b. Inhibiting factors: lack of adaptation between institutions and technology, so that the information is left behind